ANALISIS PENGARUH CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSET - Maulani, Rahmawati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study is to analyze and determine the effect of the Capital Adequacy Ratio on Return On Assets. The subject of this research is one of the banks listed on the Indonesia Stock Exchange, namely. The object of this research is the Capital Adequacy Ratio and Return On Assets. The method used is associative descriptive with a quantitative approach and analyzed using simple linear regression including the test of the coefficient of determination and partial test (t test). The test results of the determination coefficient test are 0.182 which means that the effect of Capital Adequacy Ratio on Return On Asset is 18.2%, the remaining 81.8% is influenced by other factors. Based on a simple correlation coefficient test seen from the R value of 0.427. This shows that the level of the moderate relationship between CAR and ROA. Partially seen from the test t CAR (X) has a significant effect on ROA (Y) with t count of 2.585 and significant at 0.015